Estrategias lúdicas para la estimulación del lenguaje en niños de la etnia indígena entre 4 a 5 años, de la Comunidad de Gradas – Ecuador. - Pasto Patín, Gloria Janneth (2023)
The research developed in the Intercultural Bilingual Community Educational Unit “RUMIÑAHUI” focused on indigenous children aged 4 to 5 years, seeking to strengthen their linguistic development through recreational strategies adapted to their cultural and linguistic context during the period 2021-2022. The research methodology was mixed and phenomenological in nature, using inductive, deductive and descriptive methods. The tools used included surveys and the Peabody test to measure language comprehension. Regarding results, the research confirmed that playful strategies are effective in stimulating language in children of the indigenous ethnic group, evidenced by an increase in Peabody test scores after the educational intervention. Despite facing socioeconomic challenges, with a median family income of $300 and a parental occupation focused on agriculture (46.67%), children showed improvements in language skills and verbal comprehension. However, a trend of lower mastery of the native Quichua language compared to Spanish was detected, which suggests linguistic assimilation towards Spanish in the family environment. The results support the hypothesis that recreational activities are a valuable means for language development in multilingual and multicultural contexts. It is concluded that the application of playful strategies in the “RUMIÑAHUI” Educational Unit significantly improved receptive language and verbal comprehension in indigenous children, validating the effectiveness of these culturally adapted educational practices. It is urged to promote bilingualism and strengthen the Quichua language along with Spanish through teaching materials and parental and teacher training in the Gradas community.